The decline in adult mortality in Costa Rica - Rosero Bixby, Luis (1996)
The purpose is to describe the mortality transition at adult ages, to identify its key components, and to make inferences about its likely determinants. The chapter has five sections: Socio-economic and public-health background of Costa Rica; the data and methods used; decline in risks of dying in ages 20-49 and 50-79 years; analysis of risks of dying by cause of death; and areal analysis of adult mortality and its correlate across 100 small geographical units